Soil and cacao genomics survey of Sierra Nevada de Santa Marta Region, Colombia - Libohova, Zamir; Martin Lopez, Javier Mauricio; Da Silva, Mayesse; Lagoueyte, C.; Cruz, J.; Drohan, P.; Maximova, S.; Guiltinan, M.; Ferruzzi, M.G.; Guarín, D.; Reich, P.; Kome, C.; et al. (2020)
This soil and cacao genomics survey was developed cooperatively by United States Agency for International Development (USAID) and United States Department of Agriculture (USDA) in conjunction with the International Center for Tropical Agriculture (CIAT), Pennsylvania State University, Foreign Agriculture Service (FAS), Colombian Cacao Producers Federation (FEDECACAO), and United Nations Office against Drugs and Crime (UNODC) as part of the Cacao for Peace (CfP) Initiative. The CfP seeks to improve rural well-being in Colombia through agricultural development that is inclusive and sustainable and has a positive impact on cacao farmer’s incomes, economic opportunity, stability, and peace. The CfP is analyzing soil, water, and genetic characteristics in the Sierra Nevada de Santa Marta Region. The successful implementation of the CfP initiative requires a detailed soil survey to support natural resource management and field conservation practices. The data are intended to serve as the source document for soils within the designated borders of the Sierra Nevada de Santa Marta Region. This survey contains information that affects current and future land-use planning in Sierra Nevada de Santa Marta. It contains predictions of soil behavior for selected land uses and information on major genetic groups of cacao trees. The survey highlights soil limitations, actions needed to overcome the limitations, and the impact of selected land uses on the environment. It is designed to meet the needs of Colombian farmers to better understand the properties of the soils, the genomics of the cacao plants, and the effects of these properties on various natural ecological characteristics. This knowledge can help the local cacao growers to understand, protect, and enhance the soil resources and to grow suitable cacao varieties in the region. The report is intended to identify soil properties that are used in making various land use or land treatment decisions and to identify the major cacao plant genomes in the area. Statements made in this report are intended to help the land users identify and reduce the limitations on various land uses. Soil properties that affect land use are described in this survey. The location of each map unit is shown on the detailed soil map. Each soil in the survey area is described, and information on specific uses is given. Help in using this publication and additional information are available at the International Center for Tropical Agriculture (CIAT) and online. The soil maps and field data collected and processed for the CfP initiative are available on web-based platforms and apps for portable devices, such as cellular phones. This project lays the foundation for the continuation of the CfP Initiative. The initiative supports the priorities of the Government of Colombia and works to ensure sustainable growth in the agricultural sector. The initiative has the goal of increasing farmer incomes by increasing cacao yields and improving cacao quality. Drawing upon innovations and lessons learned from the historical development of conservation in the United States, NRCS has been able to provide technical assistance and to collaborate in many ways in the planning, design, and implementation of the project.